2017
DOI: 10.1016/j.resuscitation.2016.11.017
|View full text |Cite
|
Sign up to set email alerts
|

Fibrin/fibrinogen degradation products (FDP) at hospital admission predict neurological outcomes in out-of-hospital cardiac arrest patients

Abstract: Objective: This study aimed to test the hypothesis that coagulation, fibrinolytic markers and disseminated intravascular coagulation (DIC) score (International Society on Thrombosis and Haemostasis) at hospital admission of out-of-hospital cardiac arrest (OHCA) patients can predict neurological outcomes 1 month after cardiac arrest. Results: We analyzed data for 315 patients. Except for fibrinogen level, all coagulation variables, fibrinolytic variables, and DIC score were associated with favorable neurologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 40 publications
0
31
1
Order By: Relevance
“…In addition, the TFPI levels did not match the increased levels of tissue factor from arrival at the ED to 24 hours after admission in patients with ROSC after cardiac arrest. Low levels of antithrombin were also confirmed in patients after cardiac arrest and resuscitation, especially in non‐survivors and patients with DIC . An experimental study supported these results, showing that antithrombin levels decrease with mirror‐image increases in TAT levels after CPR in a pig cardiac arrest model …”
Section: Impairment Of Anticoagulation Pathwaysmentioning
confidence: 62%
See 1 more Smart Citation
“…In addition, the TFPI levels did not match the increased levels of tissue factor from arrival at the ED to 24 hours after admission in patients with ROSC after cardiac arrest. Low levels of antithrombin were also confirmed in patients after cardiac arrest and resuscitation, especially in non‐survivors and patients with DIC . An experimental study supported these results, showing that antithrombin levels decrease with mirror‐image increases in TAT levels after CPR in a pig cardiac arrest model …”
Section: Impairment Of Anticoagulation Pathwaysmentioning
confidence: 62%
“…These results support the hypothesis that DIC is involved in organ dysfunction and a poor outcome of patients with post–cardiac arrest syndrome . In addition, the associations of DIC status, increased DIC scores and FDPs with a poor neurologic outcome were confirmed …”
Section: Dic and The Prognosis Of The Patientsmentioning
confidence: 71%
“…Antithrombin, which forms complexes with thrombin and inhibits thrombin and FXa, is one of the important anticoagulant factors. Previous studies have confirmed reduced levels of antithrombin in PCAS patients ( 11 , 52 ), particularly those with DIC ( 53 ), with a poor outcome ( 54 ), and with refractory shock ( 11 ). The reduction in the antithrombin levels may be caused by not only consumption through the formation of complexes with thrombin and protease but also extravascular loss due to increased vascular permeability ( 20 , 55 ).…”
Section: Pathophysiologymentioning
confidence: 80%
“…The systemic and sterile in ammation is the most important component of PCAS [8,25]. Second, whole-body ischemia/reperfusion induced by endothelial injury contributes to thrombotic occlusion of the vessels following activation of coagulation and impairment of brinolysis [26,27]. Several studies have demonstrated that aggregation, deformability, and the shape of RBC are altered in critical illness and different diseases [28].…”
Section: Discussionmentioning
confidence: 99%